Hubungan Pengetahuan, SIkap Ibu dengan Praktek Pemberian ASI Eksklusif Pada Bayi 0-6 Bulan - Sisilia Indriasari; Aisah Aisah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective : to analyze the relationship between the level of knowledge, the attitude of the mother and the practice of exclusive breastfeeding for bayiMethods : The study used a cross sectional design. The sampling technique used was simple random sampling with a sample size of 40 respondents. The research instrument used to assess the knowledge, attitudes and actions of exclusive breastfeeding was a questionnaire. Data processing and analysis using statistical data processing computer programs.Results : Spearman Rank Test statistic results show there is relations between maternal knowledge, attitude with exclusive breastfeeding practices for baby(p = 0.000; p= 0.001)Conclusion : knowledge and mother's attitude are important to supported the practice of exclusive breastfeeding for baby